If it's not what You are looking for type in the equation solver your own equation and let us solve it.
0.36x=(.01-x)(.01-x)
We move all terms to the left:
0.36x-((.01-x)(.01-x))=0
We add all the numbers together, and all the variables
0.36x-((-1x+0.01)(-1x+0.01))=0
We multiply parentheses ..
-((+x^2-0.01x-0.01x+0.0001))+0.36x=0
We calculate terms in parentheses: -((+x^2-0.01x-0.01x+0.0001)), so:We add all the numbers together, and all the variables
(+x^2-0.01x-0.01x+0.0001)
We get rid of parentheses
x^2-0.01x-0.01x+0.0001
We add all the numbers together, and all the variables
x^2-0.02x+0.0001
Back to the equation:
-(x^2-0.02x+0.0001)
0.36x-(x^2-0.02x+0.0001)=0
We get rid of parentheses
-x^2+0.36x+0.02x-0.0001=0
We add all the numbers together, and all the variables
-1x^2+0.38x-0.0001=0
a = -1; b = 0.38; c = -0.0001;
Δ = b2-4ac
Δ = 0.382-4·(-1)·(-0.0001)
Δ = 0.144
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0.38)-\sqrt{0.144}}{2*-1}=\frac{-0.38-\sqrt{0.144}}{-2} $$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0.38)+\sqrt{0.144}}{2*-1}=\frac{-0.38+\sqrt{0.144}}{-2} $
| 3(6p+7)=3 | | 13.12=4p | | (6x+13)=(16x7) | | 17.2=v+2 | | 17.2=v+3 | | y+1.2=11.5 | | 60=15x+19 | | s+-11.81=7.19 | | 2/3x-11=x4 | | k/4=2.93 | | 5x/6x=10 | | 0.8(x+12)=6.4 | | g-13=3.7 | | -44=6÷5x | | r-2.88=6.12 | | 5x÷6=-44 | | 2(w+36)=114 | | g+5.7=19.06 | | 10/13=n/52n | | 4y-2(y-5)=-70 | | q-1.4=5.6 | | (x)^2=8^6 | | x+2x+2x+(2x-1)+(2x-3)=76 | | n/7=15/21n | | 7=b/25 | | 2(3w-6)+2w=84 | | -a+31=3(1+a)-8a | | 20u=360 | | y=+11/5 | | g-729=-392 | | L=3w-6 | | -44=-4m |